The Role of Coastal Communities in Increasing Income through Tourism Businesses in Takalar Regency - Andi Abriani (Newinera Publisher, 2023)
This research aims to identify the actual conditions of coastal communities in Takalar Regency and determine the role of coastal communities in increasing income through tourism businesses in Takalar Regency. The type of research uses qualitative methods, namely presenting data in the form of verbal statements or descriptions of something in the form of sentences set out in writing. Meanwhile, data collection techniques use observation, interviews and documentation methods. The results of this research obtained show that the results of observations through literature studies show that Takalar Regency, with its six (6) coastal areas, is a fairly high economic booster. This is proven by field investigations that coastal areas are used for buying and selling transactions for marine products (fish, shellfish). etc.) which is quite promising. Several locations, including the Fish Auction Place (TPI), are never empty of community activities to improve the economy. This condition shows that people in coastal areas have a fairly high opportunity to improve their welfare by looking at their activities. Then, related professions or jobs, apart from being fishermen and fish sellers (traders), the people who live in coastal areas, especially the Sanrobengi area, are tourism actors with professions as restaurant owners, accommodation providers and inter-island transportation services, opportunities that can be implemented well if Entrepreneurs synergizing to carry out marketing and promotion is really needed. The government provides support and assistance through the Department of Industry and Trade, making it easier to process permits and to get to know Coastal Communities more closely in increasing Income through Tourism Businesses in Takalar district.